Indonesian midwives’ experiences in delivering childbirth services: A qualitative study - Mudy Ningrum; Desi Soraya (Journal of Healthcare Administration)
Background: Quality healthcare services during childbirth are essential for the safety of mothers and newborns. Despite global efforts to improve maternal and neonatal health, many challenges remain, particularly in low-resource settings. Midwives play a vital role in ensuring safe childbirth and improving maternal and neonatal outcomes.